Puppy - Evans, Mark, 1962- (Boston : Distributed by Houghton Mifflin, 1992)
Offers information for the first-time pet owner on the selection, care, training, and feeding of puppies.
Includes index.
Booklist.
Horn Book.
School Library Journal.
4.5.
4.5
Keywords: Dogs -- Juvenile literature; Puppies -- Juvenile literature; Dogs; Pets; Dogs; Pets